Durability for coating mortars: Review of methodologies - Gercyr Baptista Junior; Leila Celin Nascimento; Gustavo de Castro Xavier; Sérgio Neves Monteiro; Carlos Maurício Fontes Vieira; Markssuel Teixeira Marvila; Carla Therezinha Dalvi Borjaille Alledi (Journal of Materials Research and Technology, 2024)
Pathological manifestations in building systems is a complex problem from economical, cultural and environmental points of view, associated with the need of a durability analysis appears as a relevant aspect to be considered regarding the construction materials. Indeed, these materials present different degradation mechanisms, mainly with joint participation of cement. An example of these materials cementitious is the coating mortar, which has the function of protecting the structure and the sealing of the building, recognized to play a fundamental role in the constructions durability. In recent years, studies on the durability of coating mortar have intensified. In this context, this work aimed to carry out a bibliographical review of the main methods of durability analysis for coating mortar, covering the most common techniques. It was identified that the most used durability tests in coating mortars are: water absorption by capillarity and immersion, wetting and drying cycles, porosity, carbonation, freeze-thaw cycles, drying shrinkage, chloride penetration, and sulfate attack. Among them, it was verified that the most used tests are those of water absorption and accelerated aging with wetting and drying cycles. In addition, it was observed that there are significant variations between the methodologies adopted for all tests, with large discrepancies in those using aging cycles. In addition to carrying out accelerated degradation tests, it is was emphasized the need to evaluate the performance of the mortars by means of: flexural and compressive strengths, as well as mass loss, visual evaluation, dynamic modulus of elasticity, adherence, SEM and X-ray diffraction.